Bacterial Excretion of Cytoplasmic Proteins (ECP): Occurrence, Mechanism, and Function. Issue 2 (February 2019) - Ebner, Patrick; Götz, Friedrich
Abstract : The excretion of cytoplasmic and signal-peptide-less proteins (ECP) by microorganisms and eukaryotes remains a fascinating topic. In principle, it appears to be a waste of energy. However, it turns out that – extracellularly – some cytoplasmic proteins (CPs) exert a completely different function such as contributing to pathogenicity or evasion of the immune system. Such CPs have been referred to as 'moonlighting' proteins. ECP is boosted by many endogenous or external factors that impair the membrane or cell wall structure. There are also differences regarding their mode of release. In some microorganisms they appear to be released directly, while in others they are embedded in membrane vesicles, or bound to the cell envelope. Some CPs might be promising candidates for vaccine developments against major bacterial pathogens. Highlights: Cytoplasmic proteins (CPs) maintain the metabolism in living cells and therefore fulfill their main function inside the cell. Although they lack a signal peptide, they are found in the supernatants of prokaryotes and eukaryotes. The release of CPs is promoted by many factors, such as mutations, environmental changes, membrane distortion, cell-wall integrity or osmotic balance. The CPs may be released either directly into the environment or embedded in membrane vesicles. Some released CPs are immunogenic, and vaccination trials with selected antigens have yielded promising results. Some CPs show extracellular activity which differs from their intracellular activity – for example, by acting as adherence factors, killing host cells, contributing to biofilm formation, or immune evasion.